Code Switching In EFL Classroom: The Teachers’ Side Views - Agus Rahmat (British : Jurnal Bahasa dan Sastra Inggris, 2021)
The aims of this research were to find out the categories and the functions of code switching used by the English teacher of SMK Negeri 1 Makassar. This research employed descriptive qualitative research design. The participant was one of all the English teacher of SMK Negeri 1 Makassar, this participant is taken by using purposive sampling technique. The instruments were observation and audio recording. The results showed that (1) The three category of code switching mentioned by (Appel & Muysken, 2006) are found by the researcher. There are six examples of tag switching category, fourteen examples regarding with inter-sentential as well as there are thirteen examples of intra-sentential code switching found by the researcher in EFL classroom of SMK Negeri 1 Makassar; (2) The four functions mentioned by (Eldridge, 1996) are correct because the researcher found the example of equivalence in the extract one, floor-holding in the extract two, reiteration in the extract three and the last, conflict control in the extract four. It means that the researcher supports the theory of the expert regarding with the functions of code switching in EFL classroom.